Cardiac mucormycosis: a case report. Issue 3 (22nd August 2019) - Krishnappa, Darshan; Naganur, Sanjeev; Palanisamy, Dinesh; Kasinadhuni, Ganesh
Abstract: Background: Mucormycosis is an invasive fungal infection (IFI) most commonly seen in immunocompromised patients. Diabetic ketoacidosis, haematopoietic transplantation, iron overload states, and deferoxamine therapy are considered to be some of the classical risk factors. While cutaneous and rhino-sinusoidal forms may be seen in immunocompetent (IC) individuals, cardiac and mediastinal involvement is rare. In this report, we describe a young patient without predisposing factors who presented as mediastinal mucormycosis with extensive cardiac involvement. Case summary: A 19-year-old male presented with complaints of dry cough and dyspnoea on exertion over the last 4 months. Echocardiography showed diffuse infiltration of both atria along with multiple pedunculated freely mobile masses. A computed tomography chest was done to further delineate the true extent of the disease and revealed diffuse infiltration of the mediastinum, bilateral atria and interatrial septum, pulmonary veins, and superior vena cava. A fine needle aspiration cytology from a mediastinal mass revealed broad aseptate fungal hyphae with right angled branching consistent with Mucor. Extensive evaluation could not find any predisposing factors. The patient was started on Amphotericin B and surgical debridement was contemplated. However, owing to the diffuse infiltration around the heart and mediastinal vasculature, debridement could not be performed and the patient eventually succumbed to the illness. Discussion: Mediastinal mucormycosis though rare in IC patients, is a rapidly progressive condition with a high fatality. A high index of suspicion needs to be maintained in individuals presenting with infiltrative disorders of the mediastinum for early diagnosis and prompt treatment.